PENERAPAN PROTOKOL CHSE DI KAWASAN WISATA KECAMATAN DLINGO KABUPATEN BANTUL - Ajie Wicaksono; Suradi Suradi (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
The Covid-19 pandemic changes the pattern of life in the world of tourism by promoting healthy, clean, safe living habits and protecting the environment. The Ministry of Tourism and Creative Economy has regulated a protocol for handling Covid-19 in tourism objects through CHSE (Cleanliness, Health, Safety and Environmental Sustainability). One of the tourism objects that have obtained the CHSE certificate is the tourist area of Dlingo sub-district, Bantul Regency. This study uses a qualitative descriptive method, with data collection through observation, interviews with tourism object managers, and documentation. The data were then analyzed using Miles and Huberman which included data reduction, data presentation and conclusion drawing. The results showed that the tourist areas in Dlingo District, especially the Pinus Pengger Forest, Bukit Lintang Sewu, Pinus Sari Forest, Becici Peak, and Seribu Batu Songgo Langit have implemented the protocol for handling Covid-19 tourism objects that have been announced by the Ministry of Tourism and Creative Economy the concept of CHSE (Cleanliness, Health, Safety and Environmental Sustainability). This is shown by obtaining a CHSE certificate which proves that the tourist area is safe and worth visiting because it has implemented hygiene, health, security and environmentally friendly protocols.Keywords: CHSE; Tourism; Dlingo; Tourism Object; Covid-19